2007
DOI: 10.1002/cncr.22361
|View full text |Cite
|
Sign up to set email alerts
|

Research institute for nurse scientists responds to the challenge to expand and strengthen research focused on breast cancer in African American women

Abstract: In an era where scientifically derived ‘evidence’ is used as a basis for nursing practice, it is imperative that nurses have a breadth of knowledge relative to the fundamentals of nursing science; knowledge of the current standards of nursing and medical practice; and knowledge of the characteristics, needs, concerns, and challenges of diverse consumer and patient population groups. Yet, while a significant body of ‘evidence’ that describes the experiences and needs of African American women across the breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In large part, literature has focused more on prevention, early detection strategies, and the time period between diagnosis and treatment rather than how needs change across the continuum. Although numerous research efforts have been taken to address the various medical and psychosocial needs of survivors at a given point in their cancer experience, little research has been conducted on the trajectory of support needs for women from time of diagnosis to survivorship and remission (Arnold, 1999;Cappiello, Cunningham, Knobf, & Erdos, 2007;Underwood, 2007). Studies have shown, as indicated by Mullan (1985), that the cancer experience is best conceptualized as "seasons of survival" (diagnosis and treatment as the acute stage, remission as the extended stage, and permanent and end-of-life stage) (Mullan, 1985).…”
mentioning
confidence: 99%
“…In large part, literature has focused more on prevention, early detection strategies, and the time period between diagnosis and treatment rather than how needs change across the continuum. Although numerous research efforts have been taken to address the various medical and psychosocial needs of survivors at a given point in their cancer experience, little research has been conducted on the trajectory of support needs for women from time of diagnosis to survivorship and remission (Arnold, 1999;Cappiello, Cunningham, Knobf, & Erdos, 2007;Underwood, 2007). Studies have shown, as indicated by Mullan (1985), that the cancer experience is best conceptualized as "seasons of survival" (diagnosis and treatment as the acute stage, remission as the extended stage, and permanent and end-of-life stage) (Mullan, 1985).…”
mentioning
confidence: 99%